Follow the road: historical GIS for evaluating the development of routes in the Negev region during the twentieth century. Issue 6 (2nd November 2019) - Zohar, Motti
ABSTRACT: At the beginning of the twentieth century, a British mapping team led by Captain S. F. Newcombe surveyed and mapped the Negev region, Sinai, and western Jordan. The map was mainly produced for military use. Consequently, it included a network of branched routes, water supplies and facilities, and topographic contours. This study used this map to examine the development of routes in the Negev region between the beginning of and until the end of the twentieth century. First, the individual sheets comprising the study area were pieced together and the accuracy of the map was evaluated. The accuracy found on the Newcombe map was 0.76 mm on the map scale, equivalent to 100.3 m. Route development during the twentieth century was then evaluated by comparing the routes digitized from the Newcombe map to digitized routes on a late twentieth-century map. The results do not reveal tremendous changes in path, shape, or number of routes. Instead, they merely indicate the natural development in their quality. This Historical GIS-based approach provided a useful technique for analyzing and comparing the line segments extracted from historical and modern maps. The implemented approach may also serve other geographical or historical studies aiming to examine the development of branched networks throughout history.